2014
DOI: 10.1002/jctb.4443
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation of kaolin and lignin by bovine blood and hemoglobin

Abstract: BACKGROUND The kaolin flocculant activities of bovine blood (BB) and hemoglobin (HEM) at different salt and pH values were determined. Lower limit concentration (LLC), window of application (WA), and degrees of clarification (DC) values for BB and HEM were determined and compared with those of the synthetic polymeric flocculants poly(diallydimethylammonium chloride) (PDADMAC), cationic polyacrylamide (PAM), and anionic PAM. BB flocculation of lignin, a bioproduct of biomass conversion to bioethanol, was demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…Blood has a high concentration of the protein hemoglobin (Hb) and Hb is easily isolated from whole blood. Hb has been shown to be a very effective flocculant of kaolin and lignin suspensions, at relatively low doses . A major drawback of Hb‐flocculant is that its performance drops off rapidly as the pH increases above 5.5.…”
Section: Introductionmentioning
confidence: 99%
“…Blood has a high concentration of the protein hemoglobin (Hb) and Hb is easily isolated from whole blood. Hb has been shown to be a very effective flocculant of kaolin and lignin suspensions, at relatively low doses . A major drawback of Hb‐flocculant is that its performance drops off rapidly as the pH increases above 5.5.…”
Section: Introductionmentioning
confidence: 99%
“…After determining that neutral PEO was a poor co‐flocculant for HEM, a new approach was tested using positively charged poly (diallyldimethylammonium chloride) (pDADMAC) as a co‐flocculant for HEM. Previously, we showed that pDADMAC caused lignin flocculation when used in the range 15–20 mg pDADMAC g −1 lignin . Combinations of HEM and a suboptimal amount of pDADMAC (5.5 mg pDADMAC g −1 lignin) gave improved lignin flocculation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the amide I absorbance from HEM is observed at 1653 cm −1 which demonstrates that HEM is present in the lignin pellet. That HEM, the highest abundance blood protein, has a strong affinity for lignin is consistent with results from our prior research which showed that bovine blood has an affinity for lignin . Also, the binding of HEM to lignin was directly measured (see below).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear, however, that isolating Hb from the other blood components is actually advantageous. Compared to whole blood, Hb isolate may be a more potent flocculant because the less effective components are removed; indeed, a previous study compared bovine whole blood and commercially produced Hb and found that the Hb was more effective on a total solids basis. Also, removing components that do not have flocculant properties may minimize the amount of blood substances that remain in the treated water, contributing to undesirable wastewater characteristics such as turbidity, chemical oxygen demand (COD) and total Kjeldahl nitrogen (TKN) .…”
Section: Introductionmentioning
confidence: 99%